Towards a vaccine to prevent cancer in Lynch syndrome patients - Knebel Doeberitz, Magnus von; Kloor, Matthias (Familial cancer, 2013)
Germline mutations of DNA mismatch repair (MMR) genes predispose Lynch syndrome mutation carriers to the development of MMR-deficient tumors. MMR-deficient tumors show high-level microsatellite instability (MSI-H) and are typically characterized by a comparatively favorable prognosis and the absence of distant organ metastasis. Lynch syndrome-associated cancers are characterized by a pronounced local anti-tumoral immune response and usually display dense lymphocyte infiltration. This finding strongly suggested that the immune system may play an active role in the surveillance and biology of these cancers. The progression of MMR deficient cancers seems to be triggered by mutations in microsatellite sequences within gene-encoding regions. These mutations may cause shifts of the translational reading frame and thus give rise to the generation of potentially immunogenic frameshift peptides (FSP) at the carboxy terminal end of the respective gene products. FSP-specific immune responses are thought to represent one major mechanism by which the host’s adaptive immune system can recognize and potentially control Lynch syndrome-associated MSI-H cancers. Consequently, vaccination with FSP antigens represent a promising approach for treatment of Lynch syndrome-associated cancers, potentially also suitable for tumor prevention in so far tumor-free Lynch syndrome germ line mutation carriers. This review will summarize the molecular mechanisms contributing to the immunological phenotype of MSI-H cancers. In addition, clinical perspectives will be discussed, focusing on MSI-H cancer-associated FSP antigens as potential targets for immune therapy approaches.